A longitudinal cohort study on dispensed analgesic and psychotropic medications in older adults before, during, and after the COVID-19 pandemic: the HUNT study - Tanja Louise Ibsen; Ekaterina Zotcheva; Sverre Bergh; Debby Gerritsen; Gill Livingston; Hilde Lurås; Svenn-Erik Mamelund; Anne Marie Mork Rokstad; Bjørn Heine Strand; Richard C. Oude Voshaar; Geir Selbæk (BMC Geriatrics)
Abstract Background There is a growing concern and debate over the inappropriate use of analgesics and psychotropic medications by older adults, especially those with dementia. The long-term effects of the COVID-19 pandemic and lockdown measures on these prescriptions remain uncertain. Aim The primary aim was to examine changes in the prescription of analgesics (opioids and other analgesics) and psychotropics (anxiolytics/sedatives, antidepressants, and antipsychotics) in Norwegian home-dwelling older adults before, during, and up to 2 years after the COVID-19 lockdown, with a particular focus on dementia status. Secondarily, we explored individual characteristics associated with changes in medication prescriptions. Methods A prospective cohort study using baseline data from 10,464 participants (54% females, mean age 76 years [SD 5.8]) from the Norwegian Trøndelag Health Study (HUNT4 70+) linked with the Norwegian Prescription Database. Age- and education-adjusted Poisson regression was applied to examine changes in prescription fills, and multilevel mixed-effects linear regression was used to estimate the mean sum of defined daily dose (DDD) per person per period during the lockdown (March–September 2020) compared to that during the corresponding months (March–September) in 2019, 2021, and 2022. Results Overall, prescriptions of opioids, other analgesics, and anxiolytics/sedatives were higher in 2022 than during the lockdown. People without dementia had increased prescriptions of opioids, other analgesics, and antidepressants after lockdown, whereas no changes were observed among those with dementia. Increases in prescriptions of opioids, other analgesics, anxiolytics/sedatives, and antidepressants between the lockdown and 2022 occurred mainly among those aged < 80 years, without comorbidities or mental distress, with good physical function, low fear of COVID-19, and no social isolation during COVID-19. Conclusion An increase in analgesics and psychotropics after the lockdown was predominantly observed among younger-old and healthier participants. This indicates that in high-income countries, such as Norway, home-dwelling vulnerable individuals seem to have received adequate care. However, the pandemic may have increased the number of vulnerable individuals. These findings should be considered when identifying future nationwide stressors that may impair social interactions and threaten mental health. They also highlight the need to evaluate medication prescriptions for older adults after the pandemic. Trial registration The study is registered in ClinicalTrials.gov 02.02.2021, with the identification number NCT 04792086.